Inside the TV newsroom : profession under pressure : a newsroom ethnography of public service TV journalism in the UK and Denmark /: profession under pressure : a newsroom ethnography of public service TV journalism in the UK and Denmark. (2018) - Thomsen, Line Hassall
No abstract available